Rancang Bangun Dual Axis Sun Tracker Menggunakan Motor DC Power Window CSD60-B - Bagus Eko Nugroho; Erwan Eko Prasetiyo; Gaguk Marausna (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Sun tracker technology is one of the mechatronic devices to optimize the electrical energy rays from the sun's rays by directing the solar panel plane to follow the sun's direction. This research aims to design and manufacture an effective dual axis sun tracker so as to maximize the absorption of solar energy. The benefits of the research provide a design concept and a mechanical prototype of a dual axis sun tracker with a capacity of 200 Wp which is able to detect light sources using a CSD60-B DC motor in the driving system. The research method using the Conceptual Design method is a research method used in product manufacture with product development and analysis produced systematically and regularly. The results of the research on the design of a dual axis sun tracker using a DC motor CSD60-B resulted in a mechanical structural design with 3 main components, namely horizontal plane components, vertical plane components, and legs components as well as the effectiveness of the motor work applied in the product prototype. specification of horizontal plane dimensions with a length of 1494 mm, a width of 1024 mm, with the use of a shaft diameter of 57 mm and a pillow block UCP212-26 as a support for the work of the axis, a vertical plane component with a length of 1200 mm with the use of a transmission shaft of 60 mm and 2 units of pillow block UCF212 as a support for the work of the shaft, and components of the legs which have a length of 1508 mm, a width of 1008 mm, and a height of 548 mm. The effectiveness of the motor work obtained in the application in the drive system for the horizontal plane component is 123.16% and 89.38% in the vertical plane component.